Η Σμύρνη κατά τα ορλωφικά (1770): Εσωτερικές συγκρούσεις και ευρωπαϊκή παρέμβαση - Παπαδία-Λάλα, Αναστασία (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1984)
The Russian naval expedition to the Mediterranean under the Orlov brothers during the Russo-Turkish war of 1768-1774 caused tumult in the Balkans and resulted in serious consequences for the Greek populations of the Aegean basin. This paper investigates the problems confronting Smyrna —one of the largest commercial ports of the Levant, with a considerable Greek and European population— following the Ottoman naval defeat at nearby Cheshme (5-7 July 1770). The study is based on heretofore unpublished documents of the Venetian Consulate of Smyrna, as well as a large number of published documents and other sources. These sources yield new information on the massacre of over one thousand Greeks and the persecution of Christians by the Ottomans; the catastrophic effects on the European Levant trade; the deputation of the European consults of Smyrna to Alexios Orlov requesting him not to attack the city, as well as subsequent European contacts with Orlov; and the general situation in the city of Smyrna up to 1774, when the Russian fleet sailed from the Aegean. Relevant documents from the State Archives of Venice are appended to the study.